2018
DOI: 10.1002/ijc.31310
|View full text |Cite
|
Sign up to set email alerts
|

Aneustat (OMN54) has aerobic glycolysis‐inhibitory activity and also immunomodulatory activity as indicated by a first‐generation PDX prostate cancer model

Abstract: Aneustat (OMN54) is a multivalent, botanical anticancer candidate therapeutic. A recent Phase‐I clinical trial has indicated that it is well tolerated by patients and has immunomodulatory activity. In our study, using in vitro and in vivo prostate cancer models, we investigated Aneustat with regard to effects on (i) cancer‐generated immunosuppression based on aerobic glycolysis leading to acidification of the tumor microenvironment, and (ii) immune‐related processes such as macrophage differentiation and shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…Functional enrichment analysis showed that DEGs in the high‐ and low‐risk groups were highly relevant to immune‐related pathways. The immune system has a dual role in tumor development, as it can recognize and eradicate tumor cells on the one hand, while promoting tumor growth by establishing a favorable microenvironment on the other hand 36 . Moreover, the results of the GSEA analysis also support these findings.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Functional enrichment analysis showed that DEGs in the high‐ and low‐risk groups were highly relevant to immune‐related pathways. The immune system has a dual role in tumor development, as it can recognize and eradicate tumor cells on the one hand, while promoting tumor growth by establishing a favorable microenvironment on the other hand 36 . Moreover, the results of the GSEA analysis also support these findings.…”
Section: Discussionmentioning
confidence: 56%
“…The immune system has a dual role in tumor development, as it can recognize and eradicate tumor cells on the one hand, while promoting tumor growth by establishing a favorable microenvironment on the other hand. 36 Moreover, the results of the GSEA analysis also support these findings. We found that the interferonγ response was significantly more active in the high‐risk group than in the low‐risk group.…”
Section: Discussionmentioning
confidence: 58%
“… 34 Such treatment was demonstrated to have anticancer activity via inhibition of aerobic glycolysis. 35 …”
Section: Discussionmentioning
confidence: 99%
“…Aneustat (OMN54), a mixture of extracts of Ganoderma lucidum , Salvia miltiorrhiza and Scutellaria barbata , has shown favorable anticancer effect in a Phase-I Clinical Trial (NCTId: NCT01555242) ( Renouf et al, 2015 ). In vitro experiments showed that Aneustat effectively inhibited the aerobic glycolysis of LNCaP prostate cancer cells ( Qu et al, 2018 ). Silybin (SIL) is a GLUT inhibitor, and its main component is flavonoids extract from Silybum marianum .…”
Section: Introductionmentioning
confidence: 99%